Health risk analysis and risk management in the logistic-production chain as factors influencing the quality and safety of food on the example of two food companies - Orzechowska-Przybyła, Kamila; Niewelt, Alina; Lesiów, Tomasz (Analiza ryzyka zdrowotnego i zarządzanie nim w łańcuchu logistyczno-produkcyjnym jako czynniki wpływające na jakość i bezpieczeństwo żywności w dwóch firmach spożywczych, 2019)
The aim of this study was to identify risks in the quality and safety of food, and to indicate, basing on a risk analysis, the ways of managing potential risks in two different production profile enterprises of the food industry. It was found that potential hazards to the quality and safety for technological process as well as for the other links of the logistics chain were identified, and prevention procedures were established to minimize or completely eliminate these hazards. Moreover, the benefits of risk management were similar, and mainly felt in the constant increase of food producers’ awareness of the necessity of safe food production and increase of concern for the health and life of consumers. This in turn contributes to: - development of staff competence, - improvement of logistic processes to better protect against external factors, unauthorized persons and side effects, - investments and implementation of new organisational solutions in warehouses and production areas
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2019, Nr 4 (35), s. 58-78
Keywords: quality and food safety; risk analysis; risk management; logistics chain; jakość i bezpieczeństwo żywności; analiza ryzyka; zarządzanie ryzykiem; łańcuch logistyczny